Fact and fiction in economics models, realism and social construction - Mäki, Uskali (Cambridge University Press, 2002)
There is an embarrassing polarization of opinions about the status of economics as an academic discipline, as reflected in epithets such as the Dismal Science and the Queen of the Social Sciences. This collection brings together some of the leading figures in the methodology and philosophy of economics to provide a thoughtful and balanced overview of the current state of debate about the nature and limits of economic knowledge. Authors with partly rival and partly complementary perspectives examine how abstract models work and how they might connect with the real world, they look at the special nature of the facts about the economy, and they direct attention towards the academic institutions themselves and how they shape economic research. These issues are thus analysed from the point of view of methodology, semantics, ontology, rhetoric, sociology, and economics of science